The influence of the Incoming religious currents in the Algerian religious Referentiality - bennouioua, lakhdar (Journal of Social Sciences and Humanities, 2022)
We have dealt with in our article entitled “The influence of the Incoming religious currents in the Algerian religious referentiality” Shiite and Salafi organizations and their participation in a number of points that they consider a referentiality for them in dealing with the various contexts that Islamic societies know and pass through. Therefore, the twentieth century knew the birth of many organizations and currents in Various parts of the Islamic world, and behind their support were many countries and governments that adopted it as a façade to gain legitimacy, similar to Iran and Saudi Arabia. Foreign countries are not Algeria, so the lack of awareness of the differences between the homelands and the environments and the failure to consider the cultural and historical peculiarities have left the Algerian religious practice in the absolute simulations of the Incoming currents without reviewing the individual Algerian peculiarities and his social and psychological composition. The demand for identification with the Incoming traditions led to an imbalance of wisdom, as the Incoming currents did not take into account the requirements of the Algerian environment and the nature of its tools and failed to adapt to the sectarian nature of the Algerian people, and the first collision was at the level of the Referentiality where the imported religious thought failed to convince the Algerian society to change its religious practice. What led to a state of conflict with the rest of society.